2013
DOI: 10.1017/s0003598x00049802
|View full text |Cite
|
Sign up to set email alerts
|

Plant foods in the Upper Palaeolithic at Dolní Vӗstonice? Parenchyma redux

Abstract: The classic image of Upper Palaeolithic hunter-gatherers in Europe envisages them hunting large mammals in largely treeless landscapes. That is partly due to the nature of the surviving archaeological evidence, and the poor preservation of plant remains at such ancient sites. As this study illustrates, however, the potential of Upper Palaeolithic sites to yield macrofossil remains of plants gathered and processed by human groups has been underestimated. Large scale flotation of charred deposits from hearths su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
(56 reference statements)
1
17
0
1
Order By: Relevance
“…Archaeological research in the Yana Valley (27 KYA) excavations concluded those who camped at the site hunted reindeer, horses and birds29. Archaeobotanical investigations at Dolní Vĕstonice II, Czech Republic, date to 30 KYA, at a latitude below the boreal zone, revealed extensive exploitation of dietary roots and tubers30 in addition to the hunting of reindeer and mammoth.…”
Section: Discussionmentioning
confidence: 99%
“…Archaeological research in the Yana Valley (27 KYA) excavations concluded those who camped at the site hunted reindeer, horses and birds29. Archaeobotanical investigations at Dolní Vĕstonice II, Czech Republic, date to 30 KYA, at a latitude below the boreal zone, revealed extensive exploitation of dietary roots and tubers30 in addition to the hunting of reindeer and mammoth.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, agriculture tends to be seen from a semi-arid perspective; better data on forest-zone crops might well transform existing models (Blench 2006, p. 203;Blench 2007, p. 607, emphasis added). While Blench's statement overlooks the many novel archaeobotanical methods that are now available for studying vegetative crops, such as starch, phytolith, parenchyma and pollen analyses (Goude et al 2019;Haberle 1995;Lentfer 2009;Mbida Mindzié et al 2000;Power et al 2015;Pryor et al 2013), these have only rarely been applied in Africa to address the question of Asian crop introductions, and are plagued by methodological issues associated with poor preservation and uncertain taxonomic specificity. As such, linguistics remains a key method of enquiry.…”
Section: The Possible Role Of Linguisticsmentioning
confidence: 99%
“…These charcoals exhibit a cratered appearance with few discernible features, suggesting possible identification as parenchymous plant tissue (cells specialised in the storage of starch). When viewed under a scanning electron microscope, around 25 per cent of these pieces were identified as degraded conifer wood-a typical result when attempting to identify charred archaeological parenchyma (Hather 1993: 3;Pryor et al 2013). Of the remaining fragments, several exhibit partly preserved vessel elements, features that occur in flowering plants (Angiosperms) and not in the conifers that comprise the entirety of the Kostenki 11 charred wood assemblage.…”
Section: Charcoal Assemblagementioning
confidence: 99%